THE EFFECT OF GIVING CUCUMBER (Cucumis sativus) TO DECREASE HEMOGLOBIN TROMBOSITE AND IMPROVEMEN IN PRE-ECLAMMED PATIENTS AT DEWI SARTIKA HOSPITAL: Cucumber to decrease hemoglobin - Novia Sarmiati; Erwin Azizi Jaya Dipraja; La Banudi (STIKes Mandala Waluya Kendari, 2021)
Background:According to the World Health Organization (WHO) every day in 2015, around 830 women die from complications of pregnancy and child birth. Globally, maternal mortality in the world is 303,000. The maternal mortality rate (MMR) in Indonesia based on the Indonesian Health Demographic Survey (IDHS) in 2012 was around 359 / 100,000 live births, this figure increased compared to 2007, which was around 228 / 100,000 live births. Data from Dewi Sartika General Hospital with preeclampsia cases for the last three years. In 2017, the number of births in 1855 who experienced preeclampsia were 305 cases. In 2018 the number of births in 1822 who experienced preeclampsia was 334 cases. In 2019 the number of deliveries in 2007 who experienced preeclampsia was 377 cases. For 2020 January to June number of deliveries695 the incidence of preeclampsia was 164 cases. Methods:This study used a quasi-experimental type with a pre-test-post-test control group method design. The population in this study were all 164 preeclampsia patients from August to October 2020. Result:Test data analysis using testwilcoxon test (? = 0.05) in the cucumber group, it was found that p = 0.000 on decreased hemoglobin and increased platelets Conclusion:There is an effect of cucumber on decreasing hemoglobin and increasing platelets in preeclampsia patients at Dewi Sartika General Hospital.